Object Recognation Based On Genetic Algorithm With Color Segmentation - Evy Poerbaningtyas; Zusana Eko Pudyastuti (IC-ITECHS, 2014)
To be able to sort out the optimum color on an observed object is something that is very important, for example in detecting the tumor. An area which has already exposed to the tumor can be identified from the photo. Doctors typically analyze and predict the result of a photo based on their experience, but the doctors can read the photo without predicting the outcome when they use a tool that is able to distinguish color degradation. Thus, creating an artificial intelligence system can help in making a decision. A combination of generic algorithm and image processing is used to optimize color segmentation in detecting an object. In the case of color segmentation of an object, it was found that the spectrum of each color is different one to another. The color differences could be clear, unclear, or almost similar which can be used in detecting and grouping the color differences optimally.